Influence of Nanoemulsion Droplet Size of Removing Water Blocking Damage in Tight Gas Reservoir - Yuan Li; Fujian Zhou; Jie Wang; Bojun Li; Hang Xu; Erdong Yao; Longhao Zhao (Energies, 2022)
During the production process, water phase incursion into the reservoir causes water blocking damage and seriously affects the production of tight gas reservoirs. Recently, nanoemulsions have been used as highly effective water blocking removing agents in the field, but their mechanism is still unclear. In this research, a series of nanoemulsions with different droplet sizes were synthesized, and their water blocking removing performance was intensively investigated. To begin, the relationship between the droplet size and the chemical composition of the nanoemulsion was determined by dynamic light scattering. Second, the influence of the nanoemulsion droplet size on the surface tension and the contact angle experiments was studied. Finally, NMR and permeability recovery experiments were used to study the relationship between the droplet size and the water locking removing effect of the nanoemulsions. Simultaneously, the surfactant release process was investigated using the static adsorption curves of the nanoemulsions. The experimental results show that the droplet size of nanoemulsion has an exponential relationship with the oil phase content. The surface tension decreases with the increase in droplet size, but the wetting reversal effect decreases with the increase in droplet size. The nanoemulsion with an oil phase content of 5 wt.% has the best water locking removing effect, and the permeability recovery value of the core reaches 59.54%. The adsorption control of the nanoemulsion on the surfactant is the key to its water blocking removing ability. This comprehensive study shows that the nanoemulsion with an oil phase content of 5 wt.% has optimum adsorption control capability. Thus, it can be used as a promising candidate for removing water blocking in tight gas reservoirs.